20 Minute Manager Series: Giving Effective Feedback - Harvard Business Review (Harvard Business School, 2014)
As you iteract with your colleagues, direct reports, and others within your organization, are you sharing feedback with them? Communicating in the right way with others about their actions can reinforce positive behavior and move them toward more productive courses of action-outcomes that benefits everyone. This book walks you through the basicsof of giving effective, results-oriented feedback so that it can become an integral part of how work with others. You'll learn: - Recognize oppotunities for giving feedback. - Choose the best time and topics for discussion.